Expectation and evaluation of performance in the provision of occupational health nursing services - Jadloc, Sheila Marie C. (1999)
This study attempted to determine the expectation and evaluation of performance in the provision of occupational health nursing services as perceived by occupational health nurses (OHNs), employers, and employees in selected industries of Metro Manila (Muntinlupa to Novaliches), Specifically, it tested the following hypotheses:1. There is a significant difference in the expectations in occupational health nursing services among the groups of (HNs, employers, and employees;2. There is a significant difference in the evaluation of performance in the evaluation of performance regarding the provision of occupational health nursing services among the groups of OHNs, employers, and employees;3. There is a significant difference in the expectation and evaluation of performance in the provision of occupational health nursing services within each group of the OHNs, employers, and employees;The study made use of descriptive and inferential statistics such as Analysis of Variance (ANOVA) and Paired t-test using a level of significance of 0.05.Structured questionnaires were developed by the investigator based on review of manuals, articles, and previous studies as well as suggestions from experts in the field of OHN and in the academe.The respondents composed of 40 OHNs, 37 employers, and 579 employees were selected from medium and large-scale industries of Metro Manila.The first hypothesis was supported by the findings that there is a significant difference in the expectations in OHN services among the groups of nurses, employers, and employees in the curative, educative, and administrative categories. However, there is no significant difference found with respect to preventive category (F prob.=0.1164).The second hypothesis is supported by findings that there is a significant difference in the evaluation of performance regarding the provision of OHN services in all the categories of OHN services among the groups of OHNs, employers, and employees (F prob.=0.0000).The third hypothesis is also supported by the findings that there is a significant difference in the expectation and evaluation within each group of the OHNs, employers, and employees in the preventive, educative and administrative categories of OHN services. The hypothesis is not supported within the OHN group in the curative category (t=0.780).This study recommends that nurses take the challenge of being more creative in coming up with cost-effective health and safety programs, in visiting working areas and homes of employees and employers, be knowledgeable of health benefits of employees and health policies in the company, and learn how to use existing research. Management should give the nurses the opportunity and resources to see her clients in their work areas and homes.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Industrial nursing; Occupational health